Development of Islamic Bank-based Cash Waqf Management in Indonesia - Aam Slamet Rusydiana; Sherrindra Avedta (Islamic Social Finance, 2022)
Waqf as an instrument of Islamic philanthropy plays an important role not only in social but also economic aspects. This is shown from the purpose of waqf is to improve the welfare of the people and reduce wealth inequality. This study aims to find the priority aspects of cash waqf at Islamic bank or LKS-PWU (Lembaga Keuangan Syariah-Pengelola Wakaf Uang) in Indonesia. The analytical method used in this study is the Delphi method with a questionnaire. In addition, the data used in this study are the results of interviews with academics, practitioners and regulators of waqf and Islamic economics in general. Meanwhile, based on the results of the analysis, it was found that of the 23 variable aspects of the LKS-PWU cash waqf in Indonesia, 18 variables had been agreed upon by experts and only 5 variables were not agreed upon. The five variables that are not agreed upon are waqf socialization, administrative completeness, violation sanctions, time period, and management guarantees. Furthermore, from the results of calculations using the Delphi method, 3 main priority aspects of the cash waqf of LKS-PWU in Indonesia were also found, namely professional management, management productivity, and community education.